2021
DOI: 10.1021/acs.jmedchem.1c00434
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of AZD8154, a Dual PI3Kγδ Inhibitor for the Treatment of Asthma

Abstract: Starting from our previously described PI3Kγ inhibitors, we describe the exploration of structure−activity relationships that led to the discovery of highly potent dual PI3Kγδ inhibitors. We explored changes in two positions of the molecules, including macrocyclization, but ultimately identified a simpler series with the desired potency profile that had suitable physicochemical properties for inhalation. We were able to demonstrate efficacy in a rat ovalbumin challenge model of allergic asthma and in cells der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 24 publications
0
21
0
Order By: Relevance
“…Although p110γ and p110δ are preferentially expressed in immune cells, p110γ/p110δ inhibitors targeting these isoforms are reported to inhibit inflammatory activity in autoimmune and inflammatory diseases models by affecting the adaptive and innate immune response, such as collagen-induced arthritis, ovalbumin-induced asthma, microbiota-dependent colitis and systemic lupus erythematosus models (31,32), leading to potential therapeutic effects in multiple inflammatory and autoimmune diseases. Furthermore, clinical trials have also shown promising effects of PI3Kδ/γ inhibitors on immune disorders such as asthma, Sjögren's syndrome and allergic rhinitis (33)(34)(35), showing significant potential of PI3K inhibitors for clinical use. Despite this, not all PI3K inhibitors can produce a good response in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Although p110γ and p110δ are preferentially expressed in immune cells, p110γ/p110δ inhibitors targeting these isoforms are reported to inhibit inflammatory activity in autoimmune and inflammatory diseases models by affecting the adaptive and innate immune response, such as collagen-induced arthritis, ovalbumin-induced asthma, microbiota-dependent colitis and systemic lupus erythematosus models (31,32), leading to potential therapeutic effects in multiple inflammatory and autoimmune diseases. Furthermore, clinical trials have also shown promising effects of PI3Kδ/γ inhibitors on immune disorders such as asthma, Sjögren's syndrome and allergic rhinitis (33)(34)(35), showing significant potential of PI3K inhibitors for clinical use. Despite this, not all PI3K inhibitors can produce a good response in treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Data extraction of appropriate Buchwald–Hartwig amination reactions led to a similar distribution of articles to the SMCC data set (Figure ). From 57 articles and 69 reactions, ,,,, the largest proportion, again, are localized in the lowest mol % category of 0–1 mol %. There are several sources that involve the use of other metal additives (CuI and Zn­(OTf) 2 ), which skew the data, being used in 50 (0.5 equiv.)…”
Section: Buchwald–hartwig Aminationmentioning
confidence: 92%
“…As a comparison to the previous data set, ca. 15 additional papers were surveyed from the Journal of Medicinal Chemistry ( JMC ) for both SMCC reactions ,, and Buchwald–Hartwig amination reactions. , As the previous data were found from a variety of journals, although largely catalysis specific, we were interested to see how different these would be compared to papers only reported in JMC and if there was a difference in mol % and ppm catalyst levels. Finding more papers with a greater focus on catalyst usage, rather than catalyst optimization, reveals a different angle to this study.…”
Section: Further Analysis Of Selected Articles Reported In the Journa...mentioning
confidence: 99%
“…The switch from a five-membered to a six-membered lactam in N -aryl lactams leads to a change from a coplanar to an out-of-plane conformation as a result of the increased steric strain . As illustrated by the matched molecular pair of 49 and 50 , the γ-lactam 49 is, unexpectedly, more lipophilic, less soluble, and higher melting than the corresponding δ-lactam 50 …”
Section: Conformational Design By Adding a Single Carbon Atommentioning
confidence: 99%